Rules of civility - Towles, Amor (Viking, 2011)
This novel presents the story of a young woman whose life is on the brink of transformation. A chance encounter with Tinker Grey, a handsome banker, in a second-rate Greenwich Village jazz bar on New Year's Eve 1938 catapults twenty-five-year-old Wall Street secretary Katey Kontent into a year-long journey in the upper echelons of New York society, where she befriends a shy multi-millionaire, an Upper East Side ne'er-do-well, and a single-minded widow. Here in the executive suites of Conde Nast rareified environs, she will have little to rely upon other than a bracing wit and her own brand of cool nerve. She experiences firsthand the poise secured by wealth and station and the failed aspirations that lie just beow the surface. The novel offers a sparkling depiction of New York's social strata, intricate imagery and themes, a finely crafted unfoding of the unforeseen, and immensely appealing characters, the heroine in particular. -- From book jacket.